2019
DOI: 10.1039/c9ra07758h
|View full text |Cite
|
Sign up to set email alerts
|

Optoelectronic, femtosecond nonlinear optical properties and excited state dynamics of a triphenyl imidazole induced phthalocyanine derivative

Abstract: A novel zinc phthalocyanine derivative PBIPC was synthesized by incorporating a triphenyl imidazole moiety at its peripheral positions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 78 publications
0
20
0
Order By: Relevance
“…Promising novel organic molecules, possessing significant nonlinear optical (NLO) characteristics, are in high demand for various device applications in the fields of photonics, biomedical imaging, optical communications, etc., ( Anusha et al, 2015 ; Venkatram et al, 2008a ). All these organic molecules, like phthalocyanines ( Rao et al, 2000 ; Maya et al, 2003 ; Swain et al, 2014b ; Bharati et al, 2018 ; Venkatram et al, 2008b ), porphyrins, and corroles ( Anusha et al, 2012 ; Sarma et al, 2011 ) are reported frequently possessing strong third-order NLO coefficients and cross-sections ( Swain et al, 2014a ; Bhattacharya et al, 2019a ; Clavian et al, 2019 ; Katturi et al, 2020a ; Katturi et al, 2020b ; Pati et al, 2020 ; Rathi et al, 2020 ; Kumar et al, 2021 ). Phthalocyanines generally have strong colors and are used as dyes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Promising novel organic molecules, possessing significant nonlinear optical (NLO) characteristics, are in high demand for various device applications in the fields of photonics, biomedical imaging, optical communications, etc., ( Anusha et al, 2015 ; Venkatram et al, 2008a ). All these organic molecules, like phthalocyanines ( Rao et al, 2000 ; Maya et al, 2003 ; Swain et al, 2014b ; Bharati et al, 2018 ; Venkatram et al, 2008b ), porphyrins, and corroles ( Anusha et al, 2012 ; Sarma et al, 2011 ) are reported frequently possessing strong third-order NLO coefficients and cross-sections ( Swain et al, 2014a ; Bhattacharya et al, 2019a ; Clavian et al, 2019 ; Katturi et al, 2020a ; Katturi et al, 2020b ; Pati et al, 2020 ; Rathi et al, 2020 ; Kumar et al, 2021 ). Phthalocyanines generally have strong colors and are used as dyes.…”
Section: Resultsmentioning
confidence: 99%
“…To revive the study of the potential of NLO in the field of telecommunication, photonics, biomedicine, and optical signal processing, several NLO moieties were designed through various π-conjugated organic molecules ( Mardar, 2006 ; Bures et al, 2012 ; Sofiani et al, 2016 ; Biswas et al, 2020 ). For this reason, a great variety of small organic molecules and macrocyclic systems, such as porphyrins ( Rao et al, 2000 ; Senge et al, 2007 ; Swain et al, 2014a ; Katturi et al, 2020b ; Rathi et al, 2020 ; Vijisha et al, 2020 ; Kumar et al, 2021a ), phthalocyanines ( de la Torre et al, 2004 ; Kumar et al, 2007 ; Swain et al, 2014b ; Zhang et al, 2014 ; Bharati et al, 2018 ; Venkatram et al, 2018a; Venkatram et al, 2018b; Bhattacharya et al, 2019a ; Bhattacharya et al, 2019b ; Bhattacharya et al, 2021 ), corroles ( Katturi et al, 2020a ; Lu et al, 2021 ), porphycenes ( Sarma et al, 2011 ; Swain et al, 2012 ; Pati et al, 2020 ), and BODIPY dyes ( Ngoy et al, 2019 ), have been investigated for their NLO properties. Of these systems, we are particularly interested in phthalocyanine-based macrocyclic systems toward these applications.…”
Section: Introductionmentioning
confidence: 99%
“…It indicates that stimulated emission in CuPcs can increase the decay lifetime because of the unique electronic structure of Cu elements. 39,40 The decay curves divergence of all CuPcs ascribed to that different substitution, which can affect the triplet process, and probably originated from the improved molecular interaction and increase of the Forster energy transfer process, which lead to excitation coupling with π → π ⁎ transitions between closed molecules.…”
Section: Znpc Cupcmentioning
confidence: 99%
“…Together with the capacity of selectively binding cationic species, this turns imidazoles into potential optical chemosensors for a wide range of applications [12] such as pH [13,14] and cation detection [15,16]. In addition to this application, imidazole derivatives have also found application as thermally stable fluorophores for Organic Light-Emitting Diode (OLED)s [17], two-photon absorbing molecules [18], nonlinear optical materials [19], DNA intercalators [20], and PDI photosensitizers [21]. Moreover, the introduction of π bridges of a heterocyclic nature, such as sulfur five-membered heterocycles, can improve the photophysical properties and provide additional binding sites for certain ions.…”
Section: Introductionmentioning
confidence: 99%